Integrating nutrition and obesity prevention considerations into institutional investment decisions regarding food companies: Australian investment sector perspectives - Ella Robinson; Christine Parker; Rachel Carey; Anita Foerster; Miranda R Blake; Gary Sacks (BMC, 2022)
Abstract Background: There is growing recognition that current food systems are both unhealthy and unsustainable, and are increasingly shifting toward the supply and marketing of unhealthy, ultra-processed foods and beverages. Large food companies hold substantial power within food systems and present a significant barrier to progress on addressing issues related to nutrition and obesity prevention. Institutional investors (such as pension funds) play a key role in influencing corporate governance and practices, and are increasingly incorporating environmental, social and governance (ESG) considerations within investment decisions. By considering nutrition and obesity prevention, institutional investors present a potential avenue for driving increased food industry accountability for their population health impact. This study investigated views of stakeholders in the Australian investment sector on the incorporation of nutrition and obesity prevention considerations within institutional investment decision-making regarding food companies. Methods: Fifteen in-depth, semi-structured interviews were conducted in 2020-21. Participants were predominantly Australian-based, and included representatives from asset management companies, superannuation funds, ESG advisory/consultancy firms, ESG research providers, and relevant advocacy groups. Interviews examined challenges and opportunities to the integration of nutrition and obesity prevention considerations within institutional investment decision-making. Interviews were analysed using deductive thematic analysis, informed by a theoretical change model. Results: Several participants reported that their institution factored nutrition and obesity prevention considerations into their investment decisions; however, attention to nutrition-related issues was limited, generally perceived as 'niche', and not yet institutionalised. Key challenges and opportunities were identified at the employee, investment organisation, investment sector, government and non-government levels. These challenges and opportunities centred around experience and knowledge, quality and availability of ESG data and benchmarks, importance of investor coalitions, and demonstration of financial risks related to nutrition and obesity. Conclusion: There are a range of steps that could be taken to help ensure more systematic and effective consideration of issues related to nutrition and obesity prevention within institutional investment decision-making in Australia, including: (1) improved nutrition-related reporting metrics and benchmarking criteria for food companies; (2) better articulation of the financial risks that unhealthy diets and obesity pose to investors; (3) enhanced investor advocacy on unhealthy diets and obesity through investor coalitions and; (4) detailed guidance for investors on how to address unhealthy diets and obesity. Better engagement between the Australian public health community, institutional investors and government regulators is critical to drive changed investor practice in this area.